Relationship between perceived benefits and social influence towards Self Disclosure and Behavioral Intention in Web 2.0 - Geoffrey Harvey Tanakinjal; Ryan Macdonell Andrias; Stephen Laison Sondoh Jr.; Ag. Asri Ag. Ibrahim (2012)
The data gathering was conducted from September 2011 until October 2011 using Google document online survey. A total of 201 university students which comprises respondents from two faculties, Labuan School of International Business and Finance (LSIBF) and Labuan School of Informatics Science (LSIS) participated in the online survey. The main objective of the research is to explore the relationship between performance expectancy, effort expectancy and social influence towards behavioral intention as well as self-disclosure intention in Web 2.0. One of the key findings in this area of research was although an innovation or technology tool may be useful and ease to use, users may not be able to see the relevant of exposing private information about themselves to an unknown person online or even to the service provider. Furthermore, the analysis also revealed that social influence has a significant effect on self-disclosure intention. Another key finding proposed that the dimension of perceived benefits (combination of two original dimensions namely performance expectancy and effort expectancy) be used to understand users perception on Web 2.0.